Response of nine triticale genotypes to different salt concentrations at the germination and early seedling stages - Ramadan,Ebrahim; Freeg,Haytham A.; Shalaby,Nagwa; Rizk,Mosa S.; Ma,Jun; Du,Wenhua; Ibrahim,Omar M.; Alwutayd,Khairiah M.; AbdElgawad,Hamada; Jo,Ick-Hyun; El-Tahan,Amira M. (PeerJ, 2023)
Salinity stress poses a major challenge to agricultural productivity worldwide, and understanding their responses at the early growth stage is vital for devising strategies to cope with this stress. Therefore, to improve triticale productivity, this study investigated the salinity stress tolerance of different salt-tolerant triticale genotypes aiming to cultivate them on saline soils. To this end, salinity stress impacts on nine triticale genotypes, i.e., Zhongsi 1084, Gannong No. 2, Gannong No. 4, Shida No. 1, C6, C16, C23, C25 and C36 at germination and early seedling stages was evaluated. Each genotype was subjected to six treatments inducing control, 40, 80, 120, 160, and 200 mM NaCl treatments to study their effect on seedling and termination traits of the nine genotypes. Compared to the overall mean seedling vigor index, the seedling vigor index was higher in the genotypes Zhongsi 1084 and C6 (39% and 18.1%, respectively) and lower in Gannong No.2 (41%). Increasing NaCl concentrations negatively affected germination and seedling traits. Compared to other genotypes, Zhongsi 1084 had the highest mean germination rate, germination vigor index, germination percentage, mean daily germination and germination energy. It also showed the lowest relative salt injury. The relative salt injury was higher in the genotype Shida No. 1 than those in Gannong No. 2, Gannong No. 4, Shida No. 1, C16, and C36 genotypes. All genotypes exhibited desirable mean germination time except for line C6. High significant positive correlations were observed among germination rate, germination vigor index, germination percentage, mean daily germination, seedling vigor index, and root length. Principal component analysis (PCA) grouped the most desirable genotypes into two clusters. Our study determined salt stress tolerance of nine triticale genotypes at germination and early seedling stages. to select salt-tolerant genotypes that can be cultivated on saline soil or after salt irrigation.
Keywords: Genotypes; Germination rate; Salinity; Seedling stage; Seedling vigor index; Triticale